Successful management of fibrosing mediastinitis with severe vascular compromise: Report of two cases and literature review. (2020) - Argueta, Franklin; Villafuerte, David; Castaneda-Nerio, Jose; Peters, Jay; Restrepo, Carlos
Abstract: Fibrosing mediastinitis is a rare disorder characterized by the invasive proliferation of fibrous tissue within the mediastinum. This fibrosis can result in compression of intrathoracic structures including the pulmonary vasculature leading to clinical symptoms and complications like pulmonary hypertension. Here, we present two cases of young patients with fibrosing mediastinitis complicated by pulmonary artery stenosis requiring medical and endovascular management with excellent results.